Identifikasi Jenis Teripang (Holothuridea) di Pantai Vietnam sekitar Perairan Kayu Pulau Distrik Jayapura Selatan, Kota Jayapura - Albida Rante Tasak; Popi Ida Ayer; Riska Riska; Tien Nova I. Yenusi; Marten I. Sembai (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
The aim of this research is to identify the types of sea cucumbers (Holothuroidea) on the Vietnam Coast of Kayu Pulau Waters, Jayapura City. The study consists of three stages, namely the preparation, the sampling, and the identification stages. This research is undertaken by using the line transect method and the observation is carried out by a descriptive qualitative approach. The sampling is conducted randomly in two different stations along the Vietnam coast.Ã‚Â  According to this research, it is found total that there are 5 species of Holothuroidea, in which at Station I, there are four species are identified, namely Bohadschia marmorata, Bohadschia vitiensis, Holothuria atra and Holothuria scabra. Moreover, in station II, there are four species are identified such as Actinopyga miliaris, Bohadschia vitiensis, Holothuria atra and Holothuria scabra.Ã‚Â Ã‚Â